7
$\begingroup$

How can I show that for a $n \in \mathbb N$

$$e^{1-n} \leq \frac {n!}{n^n}$$

I tried using the binomial theorem like this

$$n^n \le (1+n)^n = \sum_{k=0}^n \binom nk n^k \le \sum_{k=0}^\infty \binom nk n^k = \sum_{k=0}^\infty \frac{n!}{k!(n-k)!} n^k \le \sum_{k=0}^\infty \frac{n!}{k!} n^k = n! \sum_{k=0}^\infty \frac{n^k}{k!} = n! \cdot e^n$$

which would give me

$$\frac{1}{e^n} \le \frac{n!}{n^n}$$

But I'm missing the factor of $e$ on the left side. Can you give me a hint?

$\endgroup$
  • $\begingroup$ Have you tried applying induction? $\endgroup$ – Mark Viola Jan 6 '18 at 22:43
  • $\begingroup$ Looks like Stirling's formula $\endgroup$ – Dunham Jan 6 '18 at 22:48
6
$\begingroup$

Using induction we see that for $n=1$, the inequality holds. Assume that it holds for some number $k$.

Then, using $\left(1+\frac1k\right)^k<e$, we find that

$$\begin{align} \frac{(k+1)!}{(k+1)^{k+1}}&=\frac{k!}{k^k\left(1+\frac1k\right)^k}\\\\ &\ge \frac{e^{1-k}}{e}\\\\ &=e^{1-(k+1)} \end{align}$$

And we are done!

$\endgroup$
11
$\begingroup$

\begin{align*} n^{n}=(1+(n-1))^{n}\leq n!\sum_{k=0}^{\infty}\dfrac{(n-1)^{k}}{k!}=n!\cdot e^{n-1}. \end{align*}

$\endgroup$
4
$\begingroup$

Hint: $$ \frac{\frac{(n+1)^{n+1}}{(n+1)!}}{\frac{n^n}{n!}}=\left(1+\frac1n\right)^n\lt e $$

$\endgroup$
1
$\begingroup$

Note that

$$e^{1-n}\leq \frac {n!}{n^n}\iff \frac {e^nn!}{n^n}\geq e$$

that is true $\forall n$ indeed

$$n=1 \implies \frac{e^11!}{1^1}\geq e$$

and

$$\frac{a_{n+1}}{a_n}=\frac {e^{n+1}(n+1)!}{(n+1)^{n+1}}\frac {n^n}{e^nn!}=\frac{e}{\left(1+\frac1n\right)^n}>1$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.